Evaluation of the Efficiency of the Social Welfare Information System-Next Generation (SIKS-NG) in the Distribution of Social Assistance - Sarjito, Aris (Journal of Governance and Public Affairs, 2025)
The Social Welfare Information System-Next Generation (SIKS-NG) was introduced to modernize Indonesia’s social assistance programs by addressing issues such as data inaccuracies, delays, and inefficiencies. This study evaluates the efficiency of SIKS-NG, explores key challenges in its implementation, and offers actionable recommendations for improvement. Using qualitative methods, including secondary data analysis of official reports and academic literature, the research highlights that while SIKS-NG has improved data centralization and transparency, challenges like limited digital infrastructure, capacity gaps among administrators, and weak inter-agency coordination persist. To enhance the system’s effectiveness, targeted actions such as investing in infrastructure, building local capacity, and improving data management practices are recommended. The study concludes that with strategic improvements, SIKS-NG can better fulfill its mission of delivering equitable and timely social assistance to those in need.